A development of ecological risk screening with an application to fisheries off SW England. (3rd October 2014) - Cotter, John; Lart, William; de Rozarieux, Nathan; Kingston, Al; Caslake, Richard; Le Quesne, Will; Jennings, Simon; Caveen, Alex; Brown, Mary
Abstract: A development of the ecological risk screening (ERS) technique, scale intensity and consequence analysis (SICA), is described and application to the varied fisheries and ecosystem off the southwest of England on behalf of an industry steering group (SG) is summarized. The purpose was to prioritize ecological risks systematically and consistently in relation to policy goals agreed by the SG. Scientists listed and advised on ecosystem components, their units (individual species, stocks, habitats, or communities) and attributes, as well as agents of change in the SW, their activities, and generalized effects relevant to the policy goals. A working group (WG) of fishers, fishery observers, technical advisors, and marine scientists paired each unit with the activity thought most likely to impact the most sensitive policy goal, then scored risk according to defined rules spatially, temporally, and as intensity and duration of effects. The geometric mean of the four scores, slightly adjusted for unscored factors if necessary, was the relative impact score (RIS). With this standardized method, the main aspects of risk were considered separately and independently, thereby assisting objective prioritization. Nineteen unit–activity pairs were listed as priority risks (RIS >3) in the SW region during a 2-d meeting that fully exploited the wide range of information and experience available at the WG. Socio-economics was not considered. The ERS for the SW was designed to be compatible with other similar ERSs that might be carried out for neighbouring marine regions. ERS can minimize extra monitoring needed for ecosystem management and, in principle, collaborating non-fishery agents of change could be included. By engaging all stakeholders in the setting of initial priorities for action and by assembling all available sources of information, ERS offers a useful starting point for holistic ecosystem management.